A geospatial approach to measuring regional and sub‐regional inclusive wealth: the case of resource rich West Virginia, USA*. Issue 4 (November 2015) - Ghadimi, Hodjat; Harris, Trevor; Warner, Timothy
Abstract: Inclusive wealth is a key indicator of economic sustainability and an important component in evaluating regional policy and sustainable development initiatives. Measuring capital stocks at scales below the national level is challenging and there is limited empirical research to guide individual or comparative studies. Advances in geospatial technologies including GIS and remote sensing, and the availability of well‐attributed spatial data, provide new opportunities to generate empirical wealth estimates at differing spatial granularities. Based on a case study of West Virginia, USA, this study outlines an approach for determining inclusive wealth estimates using GIS and spatial data infrastructures at sub‐regional scales of analysis.